Love in the new millennium - Canxue, 1953- (Margellos world republic of letters book., 2018)
The most ambitious work of fiction by a writer widely considered the most important novelist working in China today In this darkly comic novel, a group of women inhabits a world of constant surveillance, where informants lurk in the flowerbeds and false reports fly. Conspiracies abound in a community that normalizes paranoia and suspicion. Some try to flee-whether to a mysterious gambling bordello or to ancestral homes that can only be reached underground through muddy caves, sewers, and tunnels. Others seek out the refuge of Nest County, where traditional Chinese herbal medicines can reshape or psychologically transport the self. Each life is circumscribed by buried secrets and transcendent delusions. Can Xue's masterful love stories for the new millennium trace love's many guises-satirical, tragic, transient, lasting, nebulous, and fulfilling-against a kaleidoscopic backdrop drawn from East and West of commerce and industry, fraud and exploitation, sex and romance.